(untitled) (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: Cough in children is one of the most common presenting symptoms to pediatricians. Acute cough lasts less than 3 weeks, subacute 3-8 weeks and chronic cough more than 8 weeks. Objectives: To find out the etiology and clinical profile of chronic cough in pediatric age group. Methods: This descriptive type of cross-sectional study was carried out in the Department of Respiratory Medicine at Dhaka Shishu Hospital, Dhaka, Bangladesh from September 2017 to August 2018 for a period of one year. Purposive sampling technique was used to select the patients. Patients with the age 6 month to 12 years who were suffering from chronic cough for more than 8 weeks were included as study population. Results: Family history of asthma was found in 36(72.0%) cases. Common clinical factors like allergic rhinitis, eczema, allergic conjunctivitis, trigger agent were found in 28(56.0%), 9(18.0%), 2(4.0%) and 50(100.0%) cases respectively. Conclusion: Family history of asthma was found in majority cases of chronic cough. Allergic rhinitis, eczema, allergic conjunctivitis and trigger agent were common clinical factors associated with chronic cough patients. DS (Child) H J 2019; 35(1) : 33-36